Promising Smart Materials for Radioelectronics - V. A. Bogush; A. V. Gusinsky; V. A. Karpovich; N. A. Pevneva; V. N. Rodionova; M. M. Kasperovich; I. A. Kashko; D. V. Grapov; Yu. M. Kukut; V. A. Labunov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The investigations of a multilayer material – a polymeric radio-transparent electrically conductive film of polyaniline with a concentration of 5, 10 and 50 % by weight on a radio-transparent fiberglass substrate were carried out. Such materials are multifunctional – the material itself has the required characteristics, but when it is exposed to external electromagnetic radiation, it provides shielding functions. Electrically conductive polymer samples (polyaniline film) deposited on a fiberglass substrate have low attenuation in the 8–12 GHz transparency band, low electromagnetic radiation reflection coefficient, high conductivity and performance characteristics, as well as manufacturability.